2020
DOI: 10.1210/clinem/dgaa507
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Features and Molecular Mechanisms of ACTH-secreting Pancreatic Neuroendocrine Tumors

Abstract: Objective Pancreatic neuroendocrine tumors (pNETs) causing ectopic adrenal corticotropic hormone (ACTH) syndrome (EAS) are rare and aggressive with little known information. We aimed to elucidate the clinical features and molecular mechanisms of pNETs with EAS by methylation analysis. Methods Seven patients with ectopic ACTH-secreting pNETs who were diagnosed at Shanghai Clinical Endocrine and Metabolic Diseases Center and Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 41 publications
0
24
0
1
Order By: Relevance
“…The mean age at diagnosis is 35–38 years; not surprisingly and because VHL does not seem to be involved in hormonal secretion, most patients are asymptomatic with nonfunctional tumors. However, ectopic secretion of ACTH with paraneoplastic Cushing syndrome is possible ( 113 ). The pathogenesis of VHL pNETs differ from that of MEN1 or sporadic pNETs notably because of:…”
Section: Digestive Neuroendocrine Neoplasms In Phakomatosesmentioning
confidence: 99%
“…The mean age at diagnosis is 35–38 years; not surprisingly and because VHL does not seem to be involved in hormonal secretion, most patients are asymptomatic with nonfunctional tumors. However, ectopic secretion of ACTH with paraneoplastic Cushing syndrome is possible ( 113 ). The pathogenesis of VHL pNETs differ from that of MEN1 or sporadic pNETs notably because of:…”
Section: Digestive Neuroendocrine Neoplasms In Phakomatosesmentioning
confidence: 99%
“…In addition, surgical management was previously thought to be challenging, due to the patients’ frequently poor general conditions. In one previous case report, two patients with ACTH-producing pNENs without metastasis underwent surgery and died of surgery-related and hypercortisolism-related complications (one from pulmonary infection and one from abdominal infection) [ 6 ]. Another report described the case of a patient with an anatomically resectable ACTH-producing pNEN that could not be resected due to an uncontrolled infection; the patient died due to sepsis [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…We report the case of a patient with an ACTH-producing pNEN who suffered from postoperative infection with S. hominis even after complete resection of the tumor; our observations indicated that meticulous attention should be paid to the management of S. hominis-associated bacteremia. Herein, we have discussed why the patient With a 5-year survival rate of 35%, ACTH-producing pNENs have a high metastatic capacity and high postoperative mortality rates; compared with other functioning and nonfunctioning pNENs, ACTH-producing pNENs have a poorer prognosis [5,6]. Although the optimal primary treatment is complete resection, most patients are diagnosed in locally advanced or metastatic stages [6].…”
Section: Discussionmentioning
confidence: 99%
“…PNETs may be functional (insulinoma, gastrinoma, or glucagonoma), although the majority are non-functional ( 13 ). PNETs may secrete ACTH but are rarer than ACTH-secreting thymic neuroendocrine neoplasms and are associated with a poorer prognosis ( 14 ).…”
Section: Discussionmentioning
confidence: 99%